2015
DOI: 10.3390/jof1020154
|View full text |Cite|
|
Sign up to set email alerts
|

Is Cryptococcus gattii a Primary Pathogen?

Abstract: The two etiologic agents of cryptococcal meningoencephalitis, Cryptococcus neoformans and C. gattii, have been commonly designated as either an opportunistic pathogen for the first species or as a primary pathogen for the second species. Such a distinction has been based on epidemiological findings that the majority of patients presenting meningoencephalitis caused by C. neoformans are immunocompromised while C. gattii infection has been reported more often in immunocompetent patients. A recent report, however… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 76 publications
1
25
0
Order By: Relevance
“…Saijo et al . demonstrated that GM‐CSF antibodies are predominantly associated with infection with the C. gatti species, as reinforced by our cases, although the reason for this specific sub‐species association remains unclear . In 2013, Rosen et al .…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Saijo et al . demonstrated that GM‐CSF antibodies are predominantly associated with infection with the C. gatti species, as reinforced by our cases, although the reason for this specific sub‐species association remains unclear . In 2013, Rosen et al .…”
Section: Discussionsupporting
confidence: 57%
“…7 Saijo et al demonstrated that GM-CSF antibodies are predominantly associated with infection with the C. gatti species, as reinforced by our cases, although the reason for this specific sub-species association remains unclear. 11,12 In 2013, Rosen et al 13 screened for GM-CSF antibodies in four current and 103 archived plasma/CSF samples from HIV-negative cryptococcal meningitis patients. Neutralising GM-CSF antibodies were detected in the four current patients and an additional three archived samples, but not in healthy or disease controls.…”
Section: Discussionmentioning
confidence: 99%
“…1 It is known that C. neoformans is associated mainly with immunosuppression, especially among HIV-infected patients, while C. gattii generally causes cryptococcosis in immunocompetent patients. 2 However, some reports have demonstrated contradictory results. Recent studies from China and South Korea showed that most of cryptococcosis patients caused by C. neoformans were HIV-negative patients without other immunocompromised conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Although in our case, the patient was considered immunocompetent on the basis of classical immunological tests (immunoglobulin dosage and lymphocyte subpopulation analysis); other immune diseases, not detected by the above methods, cannot be excluded. For example, some authors report that the presence of antibodies antigranulocyte-macrophage colony-stimulating factor (GM-CSF), not investigated in our case, could be a predisposing condition for C. gattii infection [20]. Detection of anti-GM-CSF antibodies should be encouraged in cryptococcosis cases due to C. gattii strains in order to elucidate the relationship This study between the expression of this factor and the progress of the fungal disease.…”
Section: Discussionmentioning
confidence: 80%